Development of Disadcantaged, Frontier, and Outermost Villages in Manokwari - Febriyanto, Ahmad (Business Finence Analyst Co.,, 2024)
Research related to the development of Disadvantaged, Frontier, and Outermost (3T) villages needs to be improved in Indonesia. Espicially in Manokwari Regency with IDM status that still has underdeveloped and very underdeveloped villages. This research was conducted by examining the literature related to the development of underdeveloped villages. The findings show that APBD and village funds can play a role in improving the development of underdeveloped villages, accompanied by alignment of fund allocation and reduction of potential human error. In addition,domestic investment and foreign investment can also play role in improving village development, accompanied by the establishment of strict regulations and supervision of the investment process from upstream to downstream. It is expected that APBD, village funds, domestic investment, and foreign investment can play a role in changing the status of underdeveloped and very underdeveloped villages in Manokwari Regency into independent villages.